2020
DOI: 10.4103/2045-9912.296044
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of hydrogen oncology: from real world survey to real world evidence

Abstract: The use of hydrogen for cancer control has made great progress in cytology and animal experiments. With the increasing number of hydrogen products on the market, larger numbers of advanced cancer patients have participated in clinical trials or received treatment at home after purchase. Our study reported a real-world survey from 82 patients with good cancer control using hydrogen products, including real world evidence from patients who received ineffective traditional treatment, patients who received traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“… 27 30 There is increasing evidence that IDH1, closely related to the carcinogenesis mediated by HIF-1α, is the most common mutated gene in GBM. 31 32 33 The mutated IDH1 increases its level by protecting HIF-1α from degradation. In the midst of IDH1 mutant gliomas, the transcriptional activity of HIF-1α increases, intensifying the growth of gliomas.…”
Section: E Xperimental F Inding a Bout The R Oles Of H mentioning
confidence: 99%
“… 27 30 There is increasing evidence that IDH1, closely related to the carcinogenesis mediated by HIF-1α, is the most common mutated gene in GBM. 31 32 33 The mutated IDH1 increases its level by protecting HIF-1α from degradation. In the midst of IDH1 mutant gliomas, the transcriptional activity of HIF-1α increases, intensifying the growth of gliomas.…”
Section: E Xperimental F Inding a Bout The R Oles Of H mentioning
confidence: 99%
“…Numerous studies have reported the therapeutic effects of H 2 on oxidative stress and inflammation-related diseases such as ischemia and reperfusion injuries, 17 18 19 atherosclerosis, 20 21 22 metabolic diseases, 23 24 25 neurodegenerative disorders, 26 27 and cancer. 28 29 30 31 These effects of H 2 are usually attributed to its anti-oxidative, anti-inflammatory, and anti-apoptotic capabilities. Recently, H 2 supplements have been tried in the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%